Economic impacts and risks of climate change under failure and success of the Paris Agreement. Issue 1 (25th June 2021) - Estrada, Francisco; Botzen, W. J. Wouter
Abstract: The Nationally Determined Contributions (NDCs) represent the world's first effort toward the Paris Agreement goal of keeping global temperature increase well below 2 ° C and pursuing 1.5 ° C. Little is known about how much the proposed mitigation efforts can reduce the risks and economic damages from unabated climate change and about the consequences if key emitters drop the Paris Agreement. Here, we use CLIMRISK, an integrated assessment model designed to support climate policy at the global, national, and subnational scales where mitigation and adaptation policy decisions are made. We characterize the consequences of unabated climate change and the benefits of current climate policy proposals by means of probabilistic estimates of the economic damages of climate change and uni‐ and multivariate dynamic climate risk indices at a detailed spatial resolution. The results presented reveal that the economic costs and risks are highly unequally distributed between and within countries and larger than previously estimated when warming in urban areas and temporal persistence of impacts are accounted for. Costs and risks can be significantly limited by strict implementation of NDCs, but increase noticeably under noncompliance by large emitters, like the United States. Abstract : Our study aims to assess the economic impacts and risks of climate change at the different spatial scales where policymakers decide about adaptation strategies and contributions to international mitigation efforts. At the subnational level, this information can also be used to identify risk hotspots, prioritize regional actions, and trigger complementary research at the local scales to develop specific adaptation strategies.